2015
DOI: 10.1021/acsnano.5b05658
|View full text |Cite
|
Sign up to set email alerts
|

Spiders Tune Glue Viscosity to Maximize Adhesion

Abstract: Adhesion in humid conditions is a fundamental challenge to both natural and synthetic adhesives. Yet, glue from most spider species becomes stickier as humidity increases. We find the adhesion of spider glue, from five diverse spider species, maximizes at very different humidities that matches their foraging habitats. By using high-speed imaging and spreading power law, we find that the glue viscosity varies over 5 orders of magnitude with humidity for each species, yet the viscosity at maximal adhesion for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
157
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(165 citation statements)
references
References 39 publications
6
157
2
Order By: Relevance
“…Differences in diet and prey type cause striking differences in both a web's architecture and the properties of its threads (Blamires et al, 2016;Herberstein and Tso, 2011;Scharf et al, 2011;Townley et al, 2006;Tso et al, 2007), as can environmental factors such as wind (Wu et al, 2013). After a web has been spun, its frame and axial threads and its capture threads respond to daily changes in environmental conditions, with humidity having the greatest impact (Agnarsson et al, 2009;Sahni et al, 2011;Opell et al, 2011Opell et al, , 2013Stellwagen et al, 2014Stellwagen et al, , 2015Amarpuri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in diet and prey type cause striking differences in both a web's architecture and the properties of its threads (Blamires et al, 2016;Herberstein and Tso, 2011;Scharf et al, 2011;Townley et al, 2006;Tso et al, 2007), as can environmental factors such as wind (Wu et al, 2013). After a web has been spun, its frame and axial threads and its capture threads respond to daily changes in environmental conditions, with humidity having the greatest impact (Agnarsson et al, 2009;Sahni et al, 2011;Opell et al, 2011Opell et al, , 2013Stellwagen et al, 2014Stellwagen et al, , 2015Amarpuri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As explained more fully in the following paragraphs, studies of the effect of humidity on the adhesion of capture threads have concluded that they evolved to perform optimally in the humidity regime typical of a species' habitat Amarpuri et al, 2015). In characterizing this performance, these studies have used flat glass and steel contact surfaces and constant velocity extensions to ensure uniform and precise comparisons.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations